Grammatical Examples and Intrinsic Motivation in Alfiyah Learning at an Indonesian Pesantren - Siti Sulaikho -; M. Abdul Hamid; Abdul Wahab Rosyidi (The Center for Language Development, Mataram State Islamic University., 2026)
This study examines how three patterns of grammatical examples in Alfiyah instruction affect the intrinsic motivation of 46 female students in the special 3A class at Madrasah Muallimin Muallimat, Pesantren Bahrul Ulum, Tambakberas, Jombang. The three patterns include repeated vocabulary across nahwu chapters, stable simple lexico-grammatical arrangements, and unfamiliar Qur’anic verses that did not appear in the fiqh and hadith books studied by the students at the same time. This study used a quantitative one-group pretest-posttest design. Data were collected through an adapted 30-item Intrinsic Motivation Inventory after validity and reliability testing. The data were analyzed descriptively and inferentially, then interpreted through Self-Determination Theory, formal operational stage, and metalinguistic awareness. The findings show that students’ intrinsic motivation decreased from a pretest mean of 3.87 (SD = 0.42) to a posttest mean of 3.31 (SD = 0.28). The smaller posttest SD indicates that students’ responses became more homogeneous around a lower motivation level, while the difference-score SD (0.32) shows that the magnitude of decline still varied across students. A paired sample t-test confirmed a significant decline, t(45) = -11.84, p < .001, with a large effect size, dz = -1.75. The findings indicate that overly repetitive, overly simple, and weakly contextualized examples may reduce interest, cognitive challenge, and learning relatedness in Alfiyah instruction